Police work - Freed, Leonard 1929-2006; Shulman, Michael 1946-; Nourmand, Tony 1965- (RAP, Reel Art Press, 2024)
The definitive collection of Leonard Freed?s acclaimed photographs of the New York police department during the turbulent 1970s.0Magnum photographer Leonard Freed worked alongside the New York police for several years, documenting the gritty reality of life on the beat at a notorious time of soaring crime and great social unrest, with the city near bankruptcy. Of his near-decade with the police department, Freed observed that "What I saw were average people doing a sometimes boring, sometimes corrupting, sometimes dangerous and ugly and unhealthy job.? His nuanced essay has a poignancy and grace, capturing the camaraderie of officers alongside the people they are hired to protect.0Freed accompanied the NYPD on murder investigations, drug raids, public demonstrations and community outreach initiatives, as well as documenting the ordinary daily grind of the job. This reedited and redesigned take on Freed?s original 1980 book features several unseen photographs from the archive. It is a celebration of this complex and compassionate body of work, which has a social resonance and relevance in today's climate
"Police Work" by Leonard Freed was first published in 1980 (Touchstone/Simon and Schuster, New York)
Keywords: Freed, Leonard -- 1929-2006; New York, NY -- Police Department; Geschichte 1972-1979; Pressefotografie; Polizeieinsatz; Freed, Leonard; Photojournalism; Police / Pictorial works; Police; Pictorial works; Bildband